Fostering Religious Harmony: The Role of Religious Leaders in Pancasila Village, Indonesia - Majid, M. Kharis; Setiawan, Muhammad Nurrosyid Huda; Izzah, Afiyatin Nur (Prodi Studi Agama-Agama, 2024)
Differences in beliefs in Indonesia often lead to social conflicts. This study aims to identify and analyze the role of religious figures in maintaining and fostering religious harmony in Banaran Village, which has been officially designated as Pancasila Village. The method used is qualitative with a descriptive-analytical approach, conducted in Pancasila Village, Banaran, Kandangan Subdistrict, Kediri Regency. The findings show that religious leaders have a significant influence on maintaining diversity harmony through inclusive approaches and interfaith dialogue. Religious leaders not only act as spiritual leaders but also as mediators and wise problem solvers amidst differences in beliefs and traditions. Through effective communication, tolerance, and inter-religious dialogue, they have successfully built and maintained social harmony in the village. However, they also face challenges, such as internal conflicts and disparities in resource access, requiring specific strategies to ensure a peaceful and harmonious community life.